The Effectiveness of STEM-Supported Inquiry-Based Learning Approach on Conceptual Understanding of 7th Graders: Force and Energy Unit - Hasan Bakirci; Merve Gül Kirici; Yilmaz Kara (Journal of Science Learning, 2022)
This research examines the effectiveness of the STEM Supported Inquiry-Based Learning Approach on the conceptual understanding of 7th graders. In the study, a mixed-method design was adopted. The research was carried out with 64 students studying in a secondary school. The study used a Conceptual Understanding Test (CUT) and an Interview Form as data collection tools. Quantitative data obtained in the research were analyzed using ANCOVA and T-test. Qualitative data were proceeded by subjecting them to content and descriptive analysis. Examining the study results, STEM Supported Inquiry-Based Learning Approach increased students’ conceptual understanding in the experimental group and the Inquiry-Based Learning Approach in the control group. It was determined that the science teaching in the experimental group was more effective in the conceptual understanding of 7th graders. The students stated that the science teaching in the experimental group was fun, created excitement, made them feel happy, instilled cooperation and team spirit, and thought by doing and living. Depending on the results obtained from the research, it was implicated that STEM-supported education should be carried out by determining the engineering design process steps suitable for the middle school level.